Academic Supervision To Enhance Teachers' Tpack Competence - Khasanah, Nurul Uswatun; Fatoni, Achmad; Haryanto, Sigit; Assidiqi, Muadz (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2023)
The objective of this study is to investigate, elucidate, and analyze the academic oversight provided by the school principal in enhancing the proficiency of Technological Pedagogical Content Knowledge (TPACK) among teachers at SMK N 1 Karanganyar. The present study employs a qualitative study methodology utilizing a case study methodology. The data has been obtained from the paperwork provided by the statistical data informant. Various data collection procedures encompass interviews, observations, documentation, and surveys. Data analysis involves the process of reducing data, presenting data, and deriving descriptive findings. Data authenticity is achieved through the utilization of source triangulation. The research findings demonstrate the significance of TPACK competency in enhancing the overall quality of the learning process. Furthermore, the use of academic supervision has the potential to enhance the proficiency of teachers in integrating technology, pedagogy, and content knowledge (TPACK). The TPACK supervision outcomes at SMK N 1 Karanganyar, yielding an average score of 4.72, are categorized as